2015
DOI: 10.2135/cropsci2015.02.0073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Atmometers within Urban Home Lawn Microclimates

Abstract: 2359ReseaRch T urfgrasses in the United States are estimated to cover 16 to 20 million hectares, an area three times larger than any irrigated crop (Morris, 2003;Milesi et al., 2005). The total turfgrass area in the United States is likely to increase greatly as urbanization continues to expand (Alig et al., 2004). Irrigation of turfgrasses in urban areas is a common practice, creating an increasing demand for water in expanding urban areas. However, many homeowners do not understand how to manage the irrigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(52 reference statements)
2
3
0
Order By: Relevance
“…The wind speed at time of satellite overpass was high (5.9 m s −1 ) (black line in Figure 15). Similar results were found by Chen and Robinson, Gleason et al, and Peterson et al [64,65,66]. They observed that as the wind speed increased, ETr from atmometer and ETr from the Penman–Monteith (P–M) equation diverted.…”
Section: Resultssupporting
confidence: 85%
“…The wind speed at time of satellite overpass was high (5.9 m s −1 ) (black line in Figure 15). Similar results were found by Chen and Robinson, Gleason et al, and Peterson et al [64,65,66]. They observed that as the wind speed increased, ETr from atmometer and ETr from the Penman–Monteith (P–M) equation diverted.…”
Section: Resultssupporting
confidence: 85%
“…Potential ET was estimated with an atmometer (ETgage, Model A, ETgage Company) adjacent to the experimental area, and the length of irrigation time was calculated using the irrigation system precipitation rate. Peterson et al (2015) determined that ETgage estimates were strongly correlated (r 2 = 88%) with ET estimates calculated by the Penman Monteith (FAO-56-PM) empirical model when located in an open sward, similar to this experiment. In addition, Hanks et al (1976) recommends that each irrigation event be collected on intervals against the gradient to account for any wind distortion or other influences on irrigation delivery.…”
Section: Resultssupporting
confidence: 76%
“…Research demonstrated that ET r estimated with atmometers was moderately correlated ( 2 = ±0.70) with weighing lysimeters values [35,36], strongly correlated ( 2 = 0.90) with pan evaporation values [37,38], and strongly correlated ( 2 = 0.92) with agrometeorological data values, for example, [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%